2021
DOI: 10.3390/polym13223912
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Von Willebrand Factor Cleavage Site in A1A2A3-Fragment under Extreme Hydrodynamic Shear

Abstract: Von Willebrand Factor (vWf) is a giant multimeric extracellular blood plasma involved in hemostasis. In this work we present multi-scale simulations of its three-domains fragment A1A2A3. These three domains are essential for the functional regulation of vWf. Namely the A2 domain hosts the site where the protease ADAMTS13 cleavages the multimeric vWf allowing for its length control that prevents thrombotic conditions. The exposure of the cleavage site follows the elongation/unfolding of the domain that is cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 76 publications
0
19
0
Order By: Relevance
“…Modelling shear flow in all-atom MD with explicit solvent is not straightforward, 18 and we used a coarse-grained representations of the protein in implicit solvents with inclusion of hydrodynamic interactions in a lattice-Boltzmann scheme. 39–41 While we could show that a shear rate of ≈10 9 s −1 would lead to protein unfolding on a timescale similar to that of 300 pN directional force, the unfolding mechanisms were markedly different. The unfolding pathways under shear have strong similarities with those observed for thermal unfolding, which is not the case of a directional mechanical force which imposes unfolding along the end-to-end distance.…”
Section: Protein Conformational Changes Upon Forcementioning
confidence: 90%
“…Modelling shear flow in all-atom MD with explicit solvent is not straightforward, 18 and we used a coarse-grained representations of the protein in implicit solvents with inclusion of hydrodynamic interactions in a lattice-Boltzmann scheme. 39–41 While we could show that a shear rate of ≈10 9 s −1 would lead to protein unfolding on a timescale similar to that of 300 pN directional force, the unfolding mechanisms were markedly different. The unfolding pathways under shear have strong similarities with those observed for thermal unfolding, which is not the case of a directional mechanical force which imposes unfolding along the end-to-end distance.…”
Section: Protein Conformational Changes Upon Forcementioning
confidence: 90%
“…Second, the sampling problem and the limited time scale of these simulations are similar to that observed when running SMDs at experimental pulling forces. For these reasons, coarse-grained biomolecular representations in implicit solvent offer a more direct implementation of hydrodynamic effects and they grant access to longer simulation time scales. ,, Significant progress has been made in the recent years, such as the use of a lattice–Boltzmann scheme for solvent–solute hydrodynamic interactions, and improved coarse-grained models. ,, However, important challenges remain, because even long simulation time scales do not allow to observe significant conformational changes at experimental shear flows. , Employing enhanced sampling techniques, that are usually deployed in a rigorous thermodynamic framework, is not trivial when using these nonequilibrium techniques, but some interesting attempts can be noticed …”
Section: Shear-induced Conformational Changesmentioning
confidence: 99%
“…As protein conformations evolve under shear, the exposure of protein regions to the solvent changes, and the propagation of the mechanical constraints along the biomolecular structure also varies . Recent simulations have suggested that the force felt by the free end of a protein subject to a constant shear flow significantly varies along time …”
Section: Shear-induced Conformational Changesmentioning
confidence: 99%
See 2 more Smart Citations